2023
DOI: 10.3390/cells12020290
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Enhances Death in Lung Adenocarcinoma A549 Cells Exposed to Cold Atmospheric Plasma Jet

Abstract: Cold atmospheric plasma (CAP) is an intensively-studied approach for the treatment of malignant neoplasms. Various active oxygen and nitrogen compounds are believed to be the main cytotoxic effectors on biotargets; however, the comprehensive mechanism of CAP interaction with living cells and tissues remains elusive. In this study, we experimentally determined the optimal discharge regime (or semi-selective regime) for the direct CAP jet treatment of cancer cells, under which lung adenocarcinoma A549, A427 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…To achieve personalized treatment, CAP is emerging as a promising approach, as the parameters of the plasma device can be fine-tuned during the treatment to suit the patient's specific dosage. CAP has been shown to reprogram the tumor microenvironment [143][144][145], inhibit tumor growth with high selectivity, and even enhance the effectiveness of other treatment modalities like chemotherapy [146][147][148][149], immunotherapy [150,151], radiotherapy [152][153][154][155], and nanomedicine [156][157][158][159][160] with improved treatment outcomes and minimized sideeffects [161]. The self-adaptive nature of the adaptive plasma system complements the power of ML.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve personalized treatment, CAP is emerging as a promising approach, as the parameters of the plasma device can be fine-tuned during the treatment to suit the patient's specific dosage. CAP has been shown to reprogram the tumor microenvironment [143][144][145], inhibit tumor growth with high selectivity, and even enhance the effectiveness of other treatment modalities like chemotherapy [146][147][148][149], immunotherapy [150,151], radiotherapy [152][153][154][155], and nanomedicine [156][157][158][159][160] with improved treatment outcomes and minimized sideeffects [161]. The self-adaptive nature of the adaptive plasma system complements the power of ML.…”
Section: Discussionmentioning
confidence: 99%
“…In order to find out a time range of cell membrane permeability for NP uptake, we added NP-PEG-FAM to the cells 0-4 h after CAPJ treatment. Next, we focused on lung tumor cells because we have already shown molecular features of cell death under the action of CAPJ on these cell lines [41,44], and this study is a logical progression of the previous study. The use of A549 and H23 cell lines will allow us to further compare whether the molecular mechanism of cell death is altered by the addition of NPs.…”
Section: Penetration Of Nps Into Cellsmentioning
confidence: 98%
“…NCI-H23 epithelial-like lung adenocarcinoma cells (ATCC # CRL-5800) were grown in RPMI 1640 (Gibco, USA) supplemented with 10% fetal bovine serum (Sigma-Aldrich), 2 mM L-glutamine, 250 mg ml −1 amphotericin B and 100 U ml −1 penicillin/streptomycin in a humidified atmosphere containing 5% CO 2 at 37 • C. uMel1 cells were grown in α-MEM medium (Sigma-Aldrich, St. Louis, MO, USA) supplemented with 20% fetal bovine serum (GIBCO, Thermo Fisher, Waltham, MA, USA), 1x GlutaMAX TM , 250 mg ml −1 amphotericin B and 100 U ml −1 penicillin/streptomycinc, 5 µg ml −1 insulin (SCI-store, Moscow, Russia), 20 ng ml −1 EGF (SCI-store, Moscow, Russia), 1x MITO (BD Biosciences-Discovery Labware, San Jose, CA, USA). A549 and H23 cells were maintained as previously described [41]. BrCCh4e-134 cells were cultivated as previously described [40].…”
Section: For Cell Lines Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, we obtained an MCF7 human breast adenocarcinoma cell line that manifested an increased expression of EGFR. The study revealed that excessive EGFR in MCF7 cells led to the spontaneous formation of spheres under standard culture conditions [ 10 , 11 ]. MCF7-EGFR spheroids have a round shape with a well-defined outer boundary and a median diameter of 100 μm, with the size of large spheroids likely to exceed 400 μm.…”
Section: Introductionmentioning
confidence: 99%